Pengembangan Perangkat Pembelajaran Matematika Realistik Pada Konsep Pecahan Di Kelas III SD - Yuliana Batlyakru (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research aims to generate the quality of realistic mathematics learning devices and describe realistic mathematics learning effectiveness the concept of fractions in the third grade of elementary school. This research was conducted in elementary schools YPK Ebenhaezer Timika the subjects were students in grade three A and B in the academic year 2014/2015. This type of research is descriptive research which was preceded by the development of PMR. Shape design of this study is one group pretest - posttest design and one group posttest design. The trial results showed that, PMR device produced has met the criteria of good learning, that is declared "invalid" by the validator with an average of 3.7 means that PMR devices are in good category, " Practical " , which is expressed by the average teacher's ability to manage learning are in the good category with an average of 3.8 , and student activity during learning are at the limits of effective criteria , because the time spent on each activity in accordance with the ideal time planned with a tolerance of 10 % . So that the overall activity of the students declared active . Furthermore, PMR device meets the criteria of " effective " expressed by the average of students' responses to all components of the learning is 96.11 % . This means that each component of the learning received a positive response from the students . Subsequently obtained THB students completed the classical . While the implementation of PMR devices found that the ability of teachers to manage learning are in both categories with an average value of 3.80 , declared inactive student activity , student response against all tested positive for the learning component with an average of 98.44 % , and 96.67 % are students thoroughly studied in the classical style . It can be concluded that , realistic mathematics learning devices developed good quality, and realistic mathematics learning on the concept of fractional effective